Efficacy Of Tranexamic Acid in Reducing Blood Loss in Primary Total Knee Replacement - Muhammad Inaamullah Younas; Faizan Rauf; Muhammad Sheraz Mustafa; Sarmad Nasir Janjua; Shaheen Iqbal; Khurram Habib (Journal of Rawalpindi Medical College)
Objective: To determine the efficacy of tranexamic acid in reducing blood loss in primary total knee replacement.